Electromagnetic Response of Clustered Charged Particles - Ye, Wenzheng; Hu, Xiaofeng; Zhou, Shuai; Wang, Chi; Jiang, Jing; Yang, Ting; Gao, Fei (Frontiers in Materials, 2021)
Electromagnetic response of clustered charged particles is the foundation of electromagnetic waves interaction with various natural phenomena, such as sandstorm, cloud, volcano eruption. Previous studies usually employed assumption of independent charged particles, without considering the coupling between them. Here, we build up a general numerical model considering the multiple scattering effect, and test it with a charged two-particle and four-particle system. The numerical results show that independence assumption fails while the number density of clustered charged particles getting larger. This work may pave the way for deeper understanding on the electromagnetic interaction of clustered charged particles.